2008
DOI: 10.1002/jssc.200700531
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cold trap adsorbents on the gas chromatographic analysis of ambient VOCs under Peltier cooling conditions

Abstract: Original PaperThe effect of cold trap adsorbents on the gas chromatographic analysis of ambient VOCs under Peltier cooling conditionsIn this work, the relative analytical performance of the GC-based detection method was investigated with a major focus on cold trap (CT) adsorbent materials against four aromatic volatile organic compounds (VOCs) (e. g., benzene, toluene, xylene, and styrene). A series of calibration experiments were hence conducted under cryofocusing conditions formed by the Peltier cooling syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Likewise, the GC-based experiments also yielded fairly good calibration results with an exception of AA prepared in gas phase. In our previous study, the TD-GC analysis of the lighter CCs like AA was found to suffer from limited linearity depending on the sorbent material type used in the cryofocusing stage [28, 29]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, the GC-based experiments also yielded fairly good calibration results with an exception of AA prepared in gas phase. In our previous study, the TD-GC analysis of the lighter CCs like AA was found to suffer from limited linearity depending on the sorbent material type used in the cryofocusing stage [28, 29]. …”
Section: Resultsmentioning
confidence: 99%
“…The cold (or cryofocusing) trap in the TD system was packed with two sorbent materials of Tenax TA and Carbopack B at equivolume ratio. The selection of sorbents used in the present work was based on experiments done in our laboratory [28, 29]. The adsorption and desorption of the analytes in the TD system were carried out at 5°C (5 min) and 320°C (20 min), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…After the SBSE step, the twisters were introduced into a tube for thermal desorption in an automated thermal desorber turbo Matrix 650 ATD from PerkinElmer (Shenton, CT, USA). The analytes were trapped in a cold trap at -58C, conditions controlled by the Peltier cooling system [23]. Dry air was used to drive the pneumatic system and to purge the Peltier coolers on the cold trap.…”
Section: Instrumentationmentioning
confidence: 99%
“…When temperature increases, the trap capability between the sorbents and the trap objects decreases. The trapping efficiency of the adsorbent traps tends to increase exponentially with a decrease in temperature [19]. Thus, the faster the temperature increases and the higher the final temperature, the faster is the desorption speed.…”
Section: Pre-condensation Systemmentioning
confidence: 99%